Analisis Perbedaan Tingkat Discretionary Accrual Sebelum dan Sesudah Adopsi IFRS - Andwi Natasa; Tri Joko Prasetyo; Komaruddin Komaruddin (Jurnal Ilmiah ESAI, 2023)
The purpose of this study is to analyze whether there are differences in the level of discretionary accruals before and after the adoption of IFRS. In this study, only one variable is used, namely discretionary accruals. The population in this study are manufacturing companies in the consumer goods industry sector listed on the Indonesia Stock Exchange in the period 2009 to 2018 with a sampling technique using the purposive sampling method. The test method uses the one sample Kolmogorov Smirnov test because the data is normally distributed and processed using IBM SPSS Statistics 26. The results of this study indicate that there are differences in the level of discretionary accruals before and after the adoption of IFRS proved by paired sample t-test.